Trace Metal Concentrations in Marsh Profiles Under the Influence of an Emerging Delta (Atchafalaya River and Wax Lake Delta) Overlying a Several Thousand Year Old (Former)Mississippi River Delta Lobe. Issue 5 (3rd July 2016) - DeLaune, R. D.; Rinklebe, Jörg; Roberts, Harry H.; White, John R.
ABSTRACT: There are concerns over the increasing concentrations of trace metals being found in the environment. Deltas are essentially integrators of watershed contamination as they are the repositories of sediment transported from and through the watershed. In order to assess changes in trace metal concentrations transported by the Mississippi River–Atchafalaya River systems, vibracores were collected from three coastal freshwater marsh sites under the influence of the Atchafalaya River and emerging Wax Lake Delta (WLD). The cores extended to a depth of 4 m which included deposits of an earlier Mississippi River Delta lobe. C-14 dating showed an age at the lower depth corresponding to approximately 3500 years ago. Vertical profile distribution of metals and metalloids were measured and comparisons between older deposits and concentrations in recent deposits were made. Concentrations of As, Cr, Cu, Ni, Zn, Mo, V, Co, and Hg metals were measured in the profiles along with Fe, Mn, and Al. There was no significant increase in heavy metals or metalloids in recent years as compared to more than 3000-year-old sediment associated with an earlier Mississippi River Delta lobe. Results show that sediment diversion through the Wax Lake Outlet did not increase concentrations of these metals in surface marsh soils. The metal concentrations in the marsh profile were compared to ERL (effects range low) and ERM (effects range medium) values to allow an ecotoxicological assessment. Arsenic was below the ERM values but was greater than the ERL which indicate a potential toxicity under certain conditions. All other metal/metalloids measured were below ERL limits. This study suggests that planned Mississippi River sediment diversions designed to slow the rate of coastal land loss are not likely to lead to trace metals contamination.